Legal Protection for Financial Technology Services from a Maqashid Syariah Perspective - Sari, Livia Trijunita; Khoiruddin, Khoiruddin (ASAS, 2024)
Fintech currently developing in Indonesia is fintech peer-to-peer lending or what is usually called fintech lending. This fintech company uses data as one of the conditions for becoming a user of this fintech service to carry out transactions on the Fintech application. However, there are no statutory regulations governing information technology-based financial services business activities. The focus of this research problem is how to protect Fintech law in Indonesian legislation and legal protection from the perspective of Maqashid Syariah . The purpose of this research is to find out how fintech legal protection is and to find out fintech legal protection from the Maqashid Syariah Perspective. This research method uses literature study from various literature . The results of this research are that legal protection is provided by OJK Number 77/POJk.01/2016, namely regarding Information Technology-Based Money Lending and Borrowing Services, here in after referred to as POJK LPMUBTI and is contained in the Financial Services Authority Circular Letter Number 2/SEOJK.07/2014. From the perspective of Maqashid Syariah Legal Protection to protect Ad-Din, An-Nafs, An-Nash, Al-Aql, Al-Mal .Keywords: Financial Technology; Supervision; Regulations